Selective alterations in prefrontal cortical GABA neurotransmission in schizophrenia: a novel target for the treatment of working memory dysfunction - Lewis, DavidA; Volk, DavidW; Hashimoto, Takanori (Psychopharmacologia, 2004)
Disturbances in critical cognitive processes, such as working memory, are now regarded as core features of schizophrenia, but available pharmacological treatments produce little or no improvement in these cognitive deficits. Although other explanations are possible, these cognitive deficits appear to reflect a disturbance in executive control, the processes that facilitate complex information processing and behavior and that include context representation and maintenance, functions dependent on the dorsolateral prefrontal cortex (DLPFC). Studies in non-human primates indicate that normal working memory function depends upon appropriate GABA neurotransmission in the DLPFC, and alterations in markers of GABA neurotransmission are well documented in the DLPFC of subjects with schizophrenia. Thus, the purpose of this paper is to review the nature of the altered GABA neurotransmission in the DLPFC in schizophrenia, and to consider how these findings might inform the search for new treatments for cognitive dysfunction in this illness. Postmortem studies suggest that markers of reduced GABA neurotransmission in schizophrenia may be selective for, or at least particularly prominent in, the subclass of GABA neurons, chandelier cells, that provide inhibitory input to the axon initial segment of populations of pyramidal neurons. Given the critical role that chandelier cells play in synchronizing the activity of pyramidal neurons, the pharmacological amelioration of this deficit may be particularly effective in normalizing the neural network activity required for working memory function. Because GABA(A) receptors containing the a(2) subunit are selectively localized to the axon initial segment of pyramidal cells, and appear to be markedly up-regulated in schizophrenia, treatment with novel benzodiazepine-like agents with selective activity at GABA(A) receptors containing the a(2) subunit may be effective adjuvant agents for improving working memory function in schizophrenia.